THE APPLICATION OF SIX SIGMA-DMAIC METHOD TO REDUCE DEFECTS AND IMPROVE THE CARTRIDGE CASE PROCESS IN AMMUNITION COMPANY - Anggamawarti, Merlina Fitri; Pratikto, Pratikto; Sumantri, Yeni (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2022)
PT. Pindad has a superior product, namely the 5.56 mm ammunition MU5-TJ. The product performance and quality, to be better, need changes in manufacturing processes and stricter quality control. In the MU5-TJ manufacturing process, defects in the cartridge significantly contribute to defective products, reaching 48.6%. This study aimed to evaluate the causes of the defects and improve the quality of the MU5-TJ cartridge production line. The method used in this study was Six Sigma-DMAIC (Define, Measure, Analyze, Improve, Control). The quality identification showed that the gauging process contributes to 67.8% of total defects in all production lines of cartridges. The critical factors were inspection methods and machine settings. Improvements were made by implementing auto-control every 15 minutes by the operators, setting the heading and necking, edge turning, and gauging machine speed. The improvements were shown to increase the sigma level from 3.24 to 3.45 and save the cost by IDR62.372.824,00.